On the dissipation layer of radial bearings - R. O. Ayeni; S. S. Okoya; C. J. Agorzie (International Journal of Mathematics and Mathematical Sciences)
The dissipation boundary layer of certain radial bearings is identified. It is shown that, under certain conditions, the temperature outside this layer is constant.